Physiological and movement demands of Rugby League referees: Influence on penalty accuracy - Emmonds, S.; O'Hara, J.; Till, K.; Jones, B.; Brightmore, A.; Cooke, C. (The Journal of Strength and Conditioning Research, 2015)
Research into the physiological and movement demands of Rugby League (RL) referees is limited, with only 1 study in the European Super League (SL). To date, no studies have considered decision making in RL referees. The purpose of this study was to quantify penalty accuracy scores of RL referees and to determine the relationship between penalty accuracy and total distance covered (TD), high-intensity running (HIR), and heart rate per 10-minute period of match play. Time motion analysis was undertaken on 8 referees over 148 European SL games during the 2012 season using 10-Hz global positioning system analysis and heart rate monitors. The number and timing of penalties awarded was quantified using Opta Stats. Referees awarded the correct decision on 74 ± 5% of occasions. Lowest accuracy was observed in the last 10-minute period of the game (67 ± 13%), with a moderate drop (effect size = 0.86) in accuracy observed between 60-70 minutes and 70-80 minutes. Despite this, there were only small correlations observed between mean heart rate, TD, HIR efforts, and penalty accuracy. Although a moderate correlation was observed between maximum velocity and accuracy. Despite only small correlations observed, it would be rash to assume that physiological and movement demands of refereeing have no influence on decision making. More likely, other confounding variables influence referee decision-making accuracy, requiring further investigation. Findings can be used by referees and coaches to inform training protocols, ensuring training is specific to both cognitive and physical match demands.